Encyclopedia of peace education - Cromwell, Alexander (In Factis Pax: Journal of Peace Education and Social Justice, 2017)
Encyclopedia of peace education, edited by Monisha Bajaj, Charlotte, Information Age Publishing, 2008, 177 pp., US 39.99 (paperback), US 73.99 (hardcover), ISBN 978-1593118983.